2001
DOI: 10.1093/oxfordjournals.rpd.a006458
|View full text |Cite
|
Sign up to set email alerts
|

Guidance Levels in the Nordic Countries: A Preliminary Report for Selected Interventional Procedures

Abstract: The Nordic radiation protection authorities have already published recommended guidance levels for patient doses for six conventional radiological examinations. Over the past two years a similar protocol has been in progress for three interventional procedures. Measurements have been performed in 22 different hospitals in the Nordic countries on patients in the weight range 40-100 kg. The selected procedures are percutaneous transluminal coronary angioplasty (PTCA), percutaneous transluminal angioplasty (PTA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 0 publications
0
6
1
Order By: Relevance
“…A number of studies have presented patient dosimetry values in PTA (Ruiz-Cruces et al 1997;Williams 1997;McParland 1998a;Dowling and Malone 2001;Widmark et al 2001). Mean KAP values from these studies are a little lower (65.7 Gy cm Ϫ2 ) than our measurements (78.9 Gy cm Ϫ2 ) and show a much greater dispersion (1.4 -407 Gy cm Ϫ2 vs. 14 -163 Gy cm Ϫ2 in our measurements).…”
Section: Discussioncontrasting
confidence: 50%
“…A number of studies have presented patient dosimetry values in PTA (Ruiz-Cruces et al 1997;Williams 1997;McParland 1998a;Dowling and Malone 2001;Widmark et al 2001). Mean KAP values from these studies are a little lower (65.7 Gy cm Ϫ2 ) than our measurements (78.9 Gy cm Ϫ2 ) and show a much greater dispersion (1.4 -407 Gy cm Ϫ2 vs. 14 -163 Gy cm Ϫ2 in our measurements).…”
Section: Discussioncontrasting
confidence: 50%
“…This work Literature (24) This work Literature (24) Head 60 60 800 1050 Sinus 30 35 510 360 Face 30 35 510 360 Chest 15 30 480 650 Abdomen 20 35 710 780 Liver 30 35 1170 900 Pelvis 30 35 540 570 (24) Barium meal 110 25 (24) Barium enema 75 60 (24) ERCP 220 19.4 (39) Hysterosalpingography 10 4.1 (39) Cerebral angiography 50 102 (37) Coronary angiography 55 36±67 (27,37,40) Abdominal angiography 90 92 (41) Renal angiography 160 139±265 (29,37) Lower limb angiography 90 36 (41) Cardiac catheterism 122 59 (40) Stent insertion 84 64 (40) PTCA 67 90±130 (27,37,42) Valvuloplasty 149 145 (40) Angioplasty 14±155 74±108 (40) Biliary drainage 215 103±184 (37,41) Pacemaker insertion 38 22 (40) Abdominal embolisation 478 123 (37) …”
Section: Discussionmentioning
confidence: 99%
“…Although the establishment of DRLs would be very useful in view of the large range of KAP values reported during ERCP (• " Table 3), little progress has been made so far. In Nordic European countries, the DRLs proposed for ERCP do not report separately on diagnostic and therapeutic procedures [32]; in the UK, DRLs have been established for "biliary drainage/intervention" based on data collected in approximately 40 examination rooms [33]; however "biliary drainage/intervention" was not clearly defined [34]. [42]; these values are low enough to recommend no routine monitoring of extremity radiation doses.…”
Section: Radiation Doses During Ercpmentioning
confidence: 99%
“…KAP values can also be calculated using an internal algorithm that takes into account the X-ray generator settings combined with collimator data. FT has been investigated as an alternative measure for estimating KAP and/or patient E; some studies reported a good correlation [22,26,30,48], but other studies reported poor correlation [31,32]. In compliance with FDA requirements [50], up-to-date fluoroscopy equipment can provide an estimate of the cumulative dose [51].…”
Section: Patient Dose Monitoringmentioning
confidence: 99%